An investigation of Anti -Cancer Activity of Moringa Oleifera Leaves - Ali, Eman N.; Nazik, Musa (2013)

(untitled)
Moringa Oleifera have been called a 'miracle tree' for its variety uses of all parts of the tree (seeds, leaves, fruits, roots, bark).